An Investigation into the Challenges Preventing Students of Educational Administration and Planning from Using ICT for Learning in Nigeria Higher Institutions - Ogunode Niyi Jacob (Indonesian Scientific Journal, 2020)
The main purpose of this research work is to investigate the challenges preventing students of educational administration and planning from using ICT for learning in Nigeria higher institutions: a case study of university of Abuja, Nigeria. The sample for this study was all the students in university of Abuja. 50 students from each level of the department of educational administration and planning totaling 200 were randomly selected from the department using simple random sampling technique. One hypothesis and three research questions were postulated as a guide to this study and a seven sub-items questionnaire divided into two sections was used to get the required information. A simple percentage and chi-square were used to test the hypotheses at 0.95% level of significance. It was found out that there are challenges preventing students of educational administration and planning from using ICT for learning. The challenges preventing students of educational administration and planning from using ICT for learning includes; unstable power supply, lack of personal laptop or computer system, unstable ICT Network services, lack of computer literacy by the students, High cost of ICT services, poor infrastructural facilities of ICT in higher institutions and poor computer literacy of the lecturers. Base on the findings, the researchers recommends that the government should increase the funding of education in Nigeria to enable schools administrators provide necessary ICT facilities in their various schools.